Prevalence of metabolic syndrome in patients with psoriasis: a hospital-based cross-sectional study - Milčić, Danijela (Sociedade Brasileira de Dermatologia, 2017)

(untitled) (An Bras Dermatol)
BACKGROUND: Emerging epidemiological evidence suggests independent associations between psoriasis and metabolic syndrome. Objectives: The aim of the study was to examine the prevalence of metabolic syndrome and its components in patients with psoriasis, and to assess which factors may predict metabolic syndrome in these patients. METHODS: A hospital-based, cross-sectional study with 244 psoriatic patients and 163 control subjects with skin diseases other than psoriasis was conducted at the Clinic of Dermatovenerology, Clinical Center of Serbia, Belgrade, from October 2011 to October 2012. Metabolic syndrome was defined using the revised National Cholesterol Education Program Adult Treatment Panel III. Severity of psoriasis was measured by Psoriasis Area and Severity Index and Body Surface Area. RESULTS: The adjusted odds ratios (ORs) and 95% confidence intervals (CI) for psoriasis patients vs. non-psoriasis patients were 2.66 (95% CI, 1.58-4.42) for metabolic syndrome, 3.81 (95% CI, 2.30-6.31) for hypertension, 2.29 (95% CI, 1.39-3.78) for central obesity, 1.92 (95% CI, 1.08-3.41) for hyperglycemia, 1.87 (95% CI 1.18-2.96) for low high-density lipoprotein cholesterol level, and 1.42 (95% CI, 0.87-1.04) for hypertrigliceridemia. We failed to find any statistically significant association between the metabolic syndrome and clinical severity of psoriasis. Later onset and longer duration of psoriasis were predicting factors for metabolic syndrome in our patients. Study limitations: The cross-sectional design of the study does not allow us to draw directional causal inferences concerning the association between psoriasis and metabolic syndrome. Factors such as diet, alcohol consumption or mental health, which have not been evaluated in this study, may be confounders in this relation. CONCLUSION: A higher prevalence of metabolic syndrome and its components in patients with psoriasis than in controls, regardless of disease severity, emphasizes the need for early treatment and follow-up of all psoriatic patients with respect to metabolic diseases.